THE EXPRESSION OF GRADATION IN ENGLISH LITERATURE - Mahammadova Surayyoxon,; Azimova Dilobarxon Berdiali qizi, (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
The article examines the expression of gradation in English literature as a linguistic and stylistic phenomenon that plays a crucial role in meaning construction and aesthetic effect. Gradation is understood as the representation of degrees of intensity, comparison, and qualitative variation through grammatical, lexical, syntactic, and rhetorical means. The study integrates insights from linguistics, stylistics, and literary criticism to demonstrate how gradation functions across genres such as poetry, prose, and drama. Using a qualitative methodology based on close textual analysis, the article identifies recurrent patterns of intensification and progression and interprets their role in character development, emotional modulation, and narrative dynamics. The findings show that gradation operates as an interconnected system rather than an isolated grammatical category, contributing to coherence, emphasis, and reader engagement. The article highlights the interpretive value of gradation for literary analysis and suggests directions for further interdisciplinary research.